Current challenges in providing bariatric surgery in France: A nationwide study. Issue 49 (December 2016) - Czernichow, Sébastien; Paita, Michel; Nocca, David; Msika, Simon; Basdevant, Arnaud; Millat, Bertrand; Fagot-Campagna, Anne
Abstract : Abstract: Bariatric surgery is a well-accepted procedure for severe and massive obesity management. We aimed to determine trends, geographical variations, and factors influencing bariatric surgery and the choice of procedure in France in a large observational study. The Health Insurance Fund for Salaried Workers (Caisse National Assurance Maladie Travailleurs Salariés) covers about 86% of the French population. The Système National d'Information Inter-régimes de l'Assurance Maladie database contains individualized and anonymized patient data on all reimbursements for healthcare expenditure. All types of primary bariatric procedures (Roux-en-Y gastric bypass [RYGB] or omega loop, adjustable gastric banding [AGB], or longitudinal sleeve gastrectomy [LSG]) performed during 2011 to 2013 were systematically recorded. Surgical techniques performed by region of residence and age-range relative risks with 95% confidence intervals of undergoing LSG or RYGB versus AGB were computed. In 2013, LSG was performed more frequently than RYGB and AGB (57% vs 31% and 13%, respectively). A total of 41, 648 patients underwent a bariatric procedure; they were predominantly female (82%) with a mean (±standard deviation) age of 40 (±12) years and a body mass index ≥40 kg/m 2 for 68% of them. A total of 114 procedures were performed in patients younger than 18 years and 2381 procedures were performed in patients aged 60 years and older. Beneficiaries of the French universal health insurance coverage for low-income patients were more likely to undergo surgery than the general population. Large nationwide variations were observed in the type choice of bariatric surgical procedures. Significant positive predictors for undergoing RYGB compared to those for undergoing AGB were as follows: referral to a center performing a large number of surgeries or to a public hospital, older age, female gender, body mass index ≥50 kg/m 2, and treatment for obstructive sleep apnea syndrome, diabetes, or depression. Universal health insurance coverage for low-income patients was inversely correlated with the probability of RYGB. Differences in access to surgery have been observed in terms of the patient's profile, geographical variations, and predictors of types of procedures. Several challenges must be met when organizing the medical care of this growing number of patients, when delivering surgery through qualified centers while assuring the quality of long-term follow-up for all patients.